Inspectorate Organizational Capacity in Central Mamuju Regency - AM. Nur , Sri Megawati; Nara, Nurdin (LEGAL BRIEF, 2024)
This study aims to analyze the organizational capacity of the Inspectorate of Central Mamuju Regency in carrying out its supervisory and audit functions. The method used is a descriptive qualitative approach with data collected through interviews, observations, and documentation. The results of the study indicate that the capacity of human resources, infrastructure, technology, and strategic leadership play an important role in the effectiveness of supervision. Although the Inspectorate has implemented a good system, challenges such as the lack of qualified auditors and budget constraints still exist. This study recommends strengthening organizational capacity through improving human resources and adopting technology to support government transparency and accountability